The cognitive and the social components of the second language learner behaviour: instruments of assessment and theory revisited. - Figueiredo, Sandra (2018)
It was developed a research programme concerning, in one hand, to the assessment of motivational, psychological and learning (styles) profiles (1), by a scales battery (motivational, attitudinal and learning tests battery); in other hand, the assessment of cognitive achievement (2), assured by a single and well structured test, in electronic format.